Kinerja dan Verifikasi Teknik Seismik Gelombang Permukaan Terintegrasi untuk Pengukuran Modulus Elastisitas Tanah Dasar - Sri Atmaja P Rosyidi (Universitas Muhammadiyah Yogyakarta, 2010)
An integrated-spectral analysis of surface waves (ISASW) test has been recently proposed as an alternative technique in pavement evaluation and monitoring. ISASW technique is developed from the spectral analysis of surface wave (SASW) method which has been a well known nondestructive testing (NDT) for geotechnical and pavement structures. Surface wave propagation between a set of receivers were transformed to frequency domain using fast Fourier transform (FFT). Therefore, a phase spectrum was produced for measuring the time lag between receivers. A wavelet filtering on impulse response was used for constructing an enhanced phase spectrum. Using phase different method, an experimental dispersion curve was generated. Inversion analysis based on the 3-D stiffness matrix method was then performed in order to produce the shear wave velocity profile. The elastic modulus of pavement layer was calculated based on the linear elastic theory. In this paper, the performance of ISA SW measurement for determining the elastic modulus of pavement subgrade is presented in this paper. Verification on its elastic modulus obtained from ISASW technique was also conducted by using falling weight deflectometer (FWD) test. The result shows that the dispersion curves obtained in the ISASW test are sensitive to indicate the stiffness change in each layer of a pavement structure. Stiffer layer, i.e., pavement surface layer, can be indetified by the parameter of high frequency and phase velocity range; and vice versa. ISASW technique is also able to comprehensively investigate the elastic modulus of subgrade layer in exisiting pavement without any destruction. A good agreement of elastic modulus of subgrade layer from ISASW and FWD test was also pres ented.